2022
DOI: 10.1103/physrevb.105.165115
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic state in the quasi-two-dimensional organic conductor λ(BEST)2FeCl4 and the path of πd

Abstract: Studies of the quasi-two-dimensional organic conductors λ-(D) 2 MCl 4 [D = donor molecules, M = Ga, Fe] have shown that λ-(BETS) 2 GaCl 4 [BETS = bis(ethylenedithio)tetraselenafulvalene] undergoes an unconventional superconducting transition and λ-(BETS) 2 FeCl 4 undergoes a field-induced superconducting transition. In λ-type salts, the interactions between donor molecules and FeCl − 4 (π -d interactions) are important.To investigate π -d interaction, a pair of magnetic M = Fe and nonmagnetic M = Ga salts whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…13 C NMR measurements on λ-(BEDSe-TTF) 2 GaCl 4 showed that the AF transition occurred at 22 K [19]. We have reported 57 Fe Mössbauer measurements and magnetic susceptibility measurements on λ-(BEDSe-TTF) 2 FeCl 4 [20]. Although the Mössbauer measurements indicated multistep development of the internal field exerted on Fe sites below 26 K, the magnetic susceptibility measurements did not indicate a magnetic anomaly at this temperature.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…13 C NMR measurements on λ-(BEDSe-TTF) 2 GaCl 4 showed that the AF transition occurred at 22 K [19]. We have reported 57 Fe Mössbauer measurements and magnetic susceptibility measurements on λ-(BEDSe-TTF) 2 FeCl 4 [20]. Although the Mössbauer measurements indicated multistep development of the internal field exerted on Fe sites below 26 K, the magnetic susceptibility measurements did not indicate a magnetic anomaly at this temperature.…”
Section: Introductionmentioning
confidence: 69%
“…In a previous study, we compared the strengths of the π -d interaction between λ-(BEDSe-TTF) 2 FeCl 4 and λ-(BETS) 2 FeCl 4 [20]. We observed weak anisotropy of the magnetic susceptibility in λ-(BEDSe-TTF) 2 FeCl 4 [20]. By contrast, clear anisotropy was reported for λ-(BETS) 2 FeCl 4 and λ-(STF) 2 FeCl 4 [3,11].…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations